Perioperative Antibiotics in Appendicitis-Do We Need to Adjust Therapy for the Elderly? A Matched Pair Analysis - Jens Strohäker; Martin Brüschke; Nora Leser; Alfred Königsrainer; Ruth Ladurner; Robert Bachmann (MDPI AG, 2022)
(1) Background: Perioperative Antibiotics for acute complicated appendicitis are a standard of care. While there are plenty of trials for pediatric patients, data for elderly patients are scarce. The goal of our study was to evaluate whether elderly patients carry more resistant bacteria and thus have less favorable outcomes after an appendectomy that may warrant intensified perioperative antibiotic treatment (2) We present a retrospective single-center matched pair (139 patients each) analysis of perioperative and microbiological outcomes of an elderly appendicitis cohort (i.e., older than 60 years) compared with a younger adult cohort (i.e., ≤60 years). Both groups were matched one for one according to gender, duration of symptoms, c-reactive protein at presentation and whether they presented with uncomplicated or complicated appendicitis. (3) Results: After matching, complicated appendicitis was present in 76.3% of both groups. Elderly patients more frequently received preoperative diagnostic CT (p < 0.001) than the young. Both operative strategy (laparoscopic appendectomy in 92.1% each) and duration of surgery (57 vs. 56 min) were equal in both groups. Postoperative antibiotics were prescribed in ~57% for a median of 3 days in both groups and antibiotic selection was similar. The incidence of surgical site infections was higher in the young (12.2% vs. 7.9%) yet not significant. There was no difference in culture positivity or bacterial spectrum and the elderly cohort did not present with increased resistant bacterial isolates. (4) Conclusions: While overall resistant bacterial strains were rare, perioperative outcomes between the young and the elderly did not differ and did neither warrant longer nor intensified antibiotic treatment.